The relationship between safety management and patient safety culture in Cancer Treatment Centers - Maher, Ali; Monfared, Mohammad; Jafari, Mehrnoosh (Asian Pacific Journal of Environment and Cancer, 2019)
Introduction: Enhancement of patient safety represents a principle objective followed by any health system, and it is necessary to consistently monitor the patient safety culture among nurses. Adopted by health service providers, the patient safety culture is described as the acceptance and maintenance of the patient safety as a common priority and value across the organization, or representation of the common patient safety-related values, beliefs, perceptions, and attitudes among the staff at centers providing health services, as expressed in their behaviors. Given the importance of this topic, the present research investigates the state of safety management in the relationship between safety management and patient safety culture in Cancer Treatment Centers, so as to study the patient safety culture among the personnel at the hospitals. Methods: The present research plan is an applied study following a descriptive aim via a correlational methodology. Validity of the questionnaires used in this research was confirmed based on opinions of five experts, with the reliability of the results among the observers confirmed by a Cronbach’s alpha of 0.86. The statistical population included three training hospitals in the city of Kermanshah, where different departments such as management, operating rooms, nurses, and the committee of safety and incidents were investigated during 2017-2018. Results: Based on the findings of the present research, significant direct relationships were observed between the patient safety culture and safety management variables (e.g., operating room standards assessment, the committee of safety and incidents, hospitalization wards assessment, hospital accreditation score, hospital structure, and hospital organization), and an inverse relationship was obtained between the hospital occupancy rate and the patient safety culture. Conclusion: Determination of safety policies by the management, keeping the personnel well-trained, and continuous reports by the personnel tend to enhance the level of safety across a hospital, thereby adding to the safety culture and productivity of the hospital while reducing potential safety risks. Accordingly, in order to enhance patient safety, it is necessary to adequately invest on the assessment of the safety culture.